2003
DOI: 10.1159/000072071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hairless Mouse Skin Surface Temperature to Wound Severity and Maturation Time

Abstract: Skin surface temperature (SST) changes measured on live hairless mice are presented as a simple means of following wound healing. SST is generally determined by 3 factors which are the ambient temperature, the rate of water loss from the surface of the skin and the diffusion of thermal energy from the body’s core. The SST increase immediately after a burn injury reflects the amount of thermal energy absorbed by the skin surface. For burns and other injuries, the drop in SST following injury, but after thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another reason could be the massive dermatoliposclerosis, leading to a prolonged diffusion distance due to a perivascular fibrosis and sclerosis 26 . The decrease in skin temperature following injury has been demonstrated as an indication of skin barrier impairment in mouse models 27 . In horses, wound temperature was shown to be lower in limb than in trunk wounds throughout the healing process 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason could be the massive dermatoliposclerosis, leading to a prolonged diffusion distance due to a perivascular fibrosis and sclerosis 26 . The decrease in skin temperature following injury has been demonstrated as an indication of skin barrier impairment in mouse models 27 . In horses, wound temperature was shown to be lower in limb than in trunk wounds throughout the healing process 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 The decrease in skin temperature following injury has been demonstrated as an indication of skin barrier impairment in mouse models. 27 In horses, wound temperature was shown to be lower in limb than in trunk wounds throughout the healing process. 28 Therapeutic approaches like temperatureactivated dressings could be of great importance.…”
Section: Dotsmentioning
confidence: 99%
“…Gordon completed his remarkable career in skin science with papers on the transport of thalidomide derivatives across human skin with his South African colleagues, led by Jeanetta Du Plessis [65], and on wound repair [66]. The latter work performed on hairless mouse skin showed that the stratum corneum permeation by ethanol is not impaired by heat until the temperature rises over 70°C.…”
Section: Gordon Flynn - Experimental Verification and Development Of mentioning
confidence: 99%